2004
DOI: 10.1370/afm.91
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Continuity of Care and Patient Satisfaction: A Critical Review

Abstract: PURPOSE We wanted to review the medical literature regarding the relationship between interpersonal continuity of care and patient satisfaction and suggest future strategies for research on this topic.METHODS A search of the MEDLINE database from 1966 through April 2002 was conducted to fi nd articles focusing on interpersonal continuity of patient care. The resulting articles were screened to select those focusing on the relationship between interpersonal continuity in the doctor-patient relationship and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
315
1
16

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(345 citation statements)
references
References 30 publications
13
315
1
16
Order By: Relevance
“…In the outpatient setting, greater continuity has been associated with better hypertensive control, lower risk of hospitalization, fewer emergency department visits, higher patient satisfaction, and higher physician satisfaction. [1][2][3][4] Achieving continuity is difficult in the inpatient setting, where care must be provided continuously. Fletcher et al showed that between 1996 and 2006, Medicare patients experienced declining levels of physician continuity during their hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…In the outpatient setting, greater continuity has been associated with better hypertensive control, lower risk of hospitalization, fewer emergency department visits, higher patient satisfaction, and higher physician satisfaction. [1][2][3][4] Achieving continuity is difficult in the inpatient setting, where care must be provided continuously. Fletcher et al showed that between 1996 and 2006, Medicare patients experienced declining levels of physician continuity during their hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…In a review of studies examining the value of interpersonal continuity, some found consistent evidence that personal continuity is associated with increased patient satisfaction and improved adherence to preventive services. 11,12 The current study did not assess patient satisfaction but did examine some preventive services (pneumococcal and influenza vaccination) and found greater adherence with influenza recommendations among patients with a personal physician.…”
Section: Discussionmentioning
confidence: 78%
“…Over the past 2 decades, several studies have demonstrated the benefits of visit continuity. Patients who see their PCP for a high proportion of their primary care office visits are more likely to be satisfied with their care [6][7][8] , maintain relationships with their physician over time 9,10 , and have more appropriate utilization of emergency and hospital services 11,12 . Some of the evidence base, however, relies on patient-reported measures of visit continuity [13][14][15] , which might be subject to response bias.…”
Section: Introductionmentioning
confidence: 99%